Integrating Biophysical, Socio-Economic and Governance Principles Into Marine Reserve Design and Management in Mexico: From Theory to Practice - Précoma-de la Mora, Magdalena; Bennett, Nathan J.; Fulton, Stuart; Munguia-Vega, Adrian; Lasch-Thaler, Cristina; Walther-Mendoza, Mariana; Zepeda-Domínguez, José Alberto; Finkbeiner, Elena Marie; Green, Alison L.; Suárez, Alvin; Weaver, Amy Hudson; Figueroa Carranza, Ana Luisa R.; et al. (Frontiers in Marine Science, 2021)
Marine conservation design and fisheries management are increasingly integrating biophysical, socio-economic and governance considerations. Integrative approaches are adopted to achieve more effective, equitable, inclusive, and robust marine policies and practices. This paper describes a participatory process to co-produce biophysical, socio-economic, and governance principles to guide the design and management of marine reserves in three regions of Mexico: the Pacific region of the Baja California Peninsula, the Gulf of California, and the Mexican Caribbean. The process of co-producing the principles included convening a coordination team, reviewing the science, convening multi-stakeholder workshops, developing and communicating the principles with key practitioners and policy makers, and supporting uptake and application to policy and practice. Biophysical principles were related to: habitat representation and risk spreading; protecting critical, special and unique areas; incorporating connectivity; allowing time for recovery; adapting to changes in climate and ocean chemistry; and considering threats and opportunities. Socio-economic principles focused on: integrating the social context, local aspirations, and human-environment interactions; considering economic and non-economic uses, promoting an equitable distribution of costs and benefits, and respecting and maintaining cultural identity and diversity. Governance principles prioritized establishing and ensuring legitimacy and institutional continuity; implementing collaborative and adaptive management; and, promoting effective management. The paper also examines early efforts to implement the principles, next steps to promote further uptake and application in Mexico, and lessons learned from the process. Thus it provides insights into a practical process and a set of principles that are valuable to inform marine conservation and fisheries management processes elsewhere.